How is Men’s Shed Engagement Associated with Mental Health and Wellbeing Outcomes? - Guerrini, Briana (Curtin University, 2023)
Men’s Sheds are a promising approach for improving men’s health and wellbeing outcomes, although there is limited empirical evidence. This thesis investigated how engagement in Men’s Sheds is associated with mental health and wellbeing outcomes. The findings indicated that engagement in diverse activities within the Shed and social factors, such as social identification with the Shed, social connections, and support giving and receiving, were associated with wellbeing outcomes.